2022
DOI: 10.3389/fphys.2022.907667
|View full text |Cite
|
Sign up to set email alerts
|

Candidate Chemosensory Genes Identified in the Adult Antennae of Sympiezomias velatus and Binding Property of Odorant-Binding Protein 15

Abstract: Chemosensory genes play important roles in insect behaviors and have thus become potential molecular targets for pest control based on the manipulation of chemoreception-driven behaviors. The great gray weevil Sympiezomias velatus (Chevrolat) (Coleoptera: Curculionidae) is an important agricultural pest that causes serious economic losses to many crops in China, but its chemosensory genes have not been reported. Here we assembled the antennal transcriptomes of female and male adult S. velatus and revealed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 97 publications
0
7
0
Order By: Relevance
“…SvelOBP1 was one of the most abundant OBPs in the transcript level of S. velatus. The expression level of OBPs is interrelated to their physiological functions [31]. Based on the expression patterns, the dominant body part expressing SvelOBP1 was the antennae and the expression of SvelOBP1 was higher in male antennae than that in female antennae.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…SvelOBP1 was one of the most abundant OBPs in the transcript level of S. velatus. The expression level of OBPs is interrelated to their physiological functions [31]. Based on the expression patterns, the dominant body part expressing SvelOBP1 was the antennae and the expression of SvelOBP1 was higher in male antennae than that in female antennae.…”
Section: Discussionmentioning
confidence: 99%
“…These two ligands were both abundant plant volatiles with high binding affinities to insect OBPs [44,[46][47][48][49][50]. In Li's study [31], the binding affinity of SvelOBP15 with 33 plant volatiles was determined. The results showed that SvelOBP15 could bind with four plant volatiles, and it hardly bound with (Z)-hex-3-en-1-ol (K i > 16 µM).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…OcomOBP7 is not differentially expressed in male and female antennae and binds strongly to limonene, a-pinene, and ocimene, the major volatile components of Andromeda, suggesting that OcomOBP7 is involved in host localization processes [15]. SvelOBP15 is not differentially expressed in either sex and has a high binding affinity for linalool, nerolidol, and limonene, suggesting that it exerts its olfactory function by binding transported plant volatiles [69]. Similarly, RproOBP6 and RproOBP13 were expressed in both male and female antennae, indicating that they probably participate in behaviors common to both sexes, such as host localization and the avoidance of natural enemies [20].…”
Section: Obp Gene Identification and Expression Profilingmentioning
confidence: 99%